PENGARUH KOMBINASI ENZIM DAN BUNGKIL INTI SAWIT TERHADAP KESERAGAMAN TUMBUH, LIVEBILITAS, INCOME OVER FEED DAN CHICK COST AYAM BROILER - Ummiani Hatta; Burhanudin Sundu; Andi Pertiwi Damayanti (Universitas Tadulako, 2010)
The objective of this study was to determine the effect of combination of enzyme and palm kernel meal on growth uniformity, liveability and income over feed and chick cost of broiler. A completely randomized design was used in this study, with 7 treatments and 5 replicated cages of 6 birds pei café. A total of 210 day – old broiler chicks were used in this study. Treatments tested were Ro = 0 % palm kernel meal (PKM), R1= 20 % PKM ,R2= 20 % PKM plus 0.02 % multi enzyme, R3 = 20 % enzymatically predigested PKM, R4 = 30 % PKM , R5 = 30 % PKM plus 0,02 % multi enzyme and R6 = 30 % enzimatically predigested PKM. Results of variance analysis indicated that addition of enzyme in palm kernel meal based diets produced non–significant difference in growth uniformity and liveability (P>0,05). Income over feed and chick cost, however, was significantly affected by enzyme addition (P<0,01 ).